Anti-sticking spiral micro-nano robot based on bio-enzyme modification and preparation method of anti-sticking spiral micro-nano robot
By modifying bioenzymes on the surface of the spiral micro-nano robot, using hyaluronidase to catalyze the decomposition of hyaluronic acid, the problem of micro-nano robots being difficult to drive in viscous biological fluids is solved, and high efficiency in complex biological fluids is achieved Controllable exercise and drag reduction effects are suitable for targeted drug delivery in the field of biomedical medicine.
Patent Information
- Application Number
- CN202411179081.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-27
AI Technical Summary
In a highly complex biological fluid environment, the controllability and stability of micro-nano robots are affected by high viscosity in viscous complex environments, adhesion of biological protein molecules, blocking effects of blood cells, flow effects of liquids and immune system. The influence of factors such as phagocytosis leads to difficulty in driving and poor controllability.
By performing biological enzyme modification on the surface of the spiral micro-nano robot, modifying the amino group by using gold sulfur bond reaction, and connecting hyaluronidase (HAase) with glutaraldehyde to catalyze the decomposition of hyaluronic acid and achieving reduction in viscous solution Resist movement. The method includes evaporating Fe and Ti layers to impart magnetic and biocompatibility, followed by gold film modification and enzyme ligation on the surface to form an anti-viscosmic helical micro-nano robot based on bioenzyme modification.
It significantly improves the anti-viscosity and drag reduction effect of micro-nano robots in viscous biological fluids, and realizes efficient and controllable driving in complex biological fluids, especially in environments such as cerebrospinal fluid, vitreous and articular fluids, providing Possibility of targeted drug delivery.
Smart Images

Figure CN119141508A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of micro-nano structure surface biological modification, and in particular to an anti-adhesive helical micro-nano robot based on biological enzyme modification and a preparation method thereof. Background Art
[0002] Helical micro-nano robots (H-MNMs) have the characteristics of small size, light weight, and strong driving force. They have broad application prospects in the biomedical field, such as achieving directional movement in complex physiological environments, improving tissue permeability, promoting cell uptake, carrying and releasing drugs, etc.
[0003] However, in a highly complex biological fluid environment, factors such as high viscosity, adhesion of biological protein molecules, blocking effect of blood cells, flow effect of liquids, phagocytosis of the immune system, etc. will also significantly affect the controllability and stability of microrobot motion. Therefore, how to achieve efficient driving of micro-nano robots in viscous and complex biological fluids is an important issue in the field. Summary of the invention
[0004] In response to the above technical problems, the present invention discloses an anti-adhesive helical micro-nano robot based on bio-enzyme modification and a preparation method thereof, which has obvious anti-adhesive and drag-reducing effects in viscous biological fluids and can solve the problems of difficult driving and poor controllability of traditional micro-nano robots in viscous and complex biological fluids.
[0005] To this end, the technical solution adopted by the present invention is:
[0006] A method for preparing an anti-adhesive helical micro-nano robot based on bioenzyme modification comprises the following steps:
[0007] Step S1, preparing a spiral micro-nano robot, and sequentially evaporating a layer of Fe and a layer of Ti on the surface of the spiral micro-nano robot to obtain a magnetically controlled spiral micro-nano robot;
[0008] Step S2, coating a layer of gold film on the surface of the magnetically controlled spiral micro-nano robot, then immersing it in a β-mercaptoethylamine solution for reaction, modifying a layer of amino groups on the spiral surface through a gold-sulfur bond reaction, and then connecting hyaluronidase to the spiral surface of the spiral micro-nano robot with glutaraldehyde to obtain an anti-adhesive spiral micro-nano robot based on biological enzyme modification.
[0009] The spiral micro-nano robot using this technical solution has biocompatibility. By modifying the biological enzyme on the surface of the spiral micro-nano robot and connecting hyaluronidase on the surface, the hyaluronidase can catalyze the decomposition of HA, thereby realizing the drag-reducing movement of the spiral micro-nano robot in a viscous solution. This is of great significance for realizing the efficient driving effect of the micro-nano robot in the actual biomedical field.
[0010] As a further improvement of the present invention, in step S1, a spiral micro-nano robot is printed on a glass sheet using a 3D printer, and then a layer of Fe and Ti is sequentially evaporated on the glass sheet using a high vacuum electron beam evaporation coating machine. Further, the spiral micro-nano robot has a diameter of 4.5-6 μm and a length of 15-20 μm.
[0011] As a further improvement of the present invention, step S1 includes: using IP-S photoresist to print a double spiral array on a glass sheet, setting the laser power to 40mW, the scanning speed to 100mm / s, and developing and drying with isopropyl alcohol after printing.
[0012] As a further improvement of the present invention, the step S1 includes: using a high vacuum electron beam evaporation coating machine to evaporate an 80nm Fe layer, and then evaporate a 10nm Ti layer; during the evaporation process, the vacuum degree is controlled at 10 -4 Hereinafter, the sample stage rotation speed is 6-10 rpm. Further, the sample stage rotation speed is 8 rpm.
[0013] As a further improvement of the present invention, in step S2, a layer of gold film is plated on the glass sheet treated in step S1, and then the glass sheet is immersed in a 5-15 μM β-mercaptoethylamine solution for reaction for more than 3 hours to modify the amino group on the spiral surface to obtain an amino-modified glass sheet; then the amino-modified glass sheet is placed in a PBS solution of glutaraldehyde for reaction for more than 3 hours, and after rinsing, a PBS solution of hyaluronidase (HAase) is added to react overnight. Further, the material sheet is rinsed with pure water 3-5 times. Further, the HAase selects a concentrated high-activity (3000U / mg) sample produced by Shanghai Yuanye.
[0014] As a further improvement of the present invention, the PBS solution of glutaraldehyde is prepared by mixing glutaraldehyde and PBS solution in a volume ratio of 1:60-80, wherein the concentration of the PBS solution is 2-3 mg / mL.
[0015] As a further improvement of the present invention, step S2 further includes: cutting the processed spiral micro-nano robot with a glass cutter and placing it in a container, adding water, and ultrasonically dispersing to obtain a spiral dispersion.
[0016] The present invention discloses an anti-adhesive helical micro-nano robot based on biological enzyme modification, which is prepared by using any one of the preparation methods of the anti-adhesive helical micro-nano robot based on biological enzyme modification as described above.
[0017] The present invention discloses the application of the anti-adhesive helical micro-nano robot based on bioenzyme modification as described above, which is used to prepare a helical micro-nano robot that can achieve efficient and controllable movement in a viscous biological fluid containing HA, and can achieve targeted drug delivery. The anti-adhesive helical micro-nano robot based on bioenzyme modification can be set according to the concentration of HA in the viscous biological fluid. Furthermore, the diameter of the helical micro-nano robot is 4.5 μm and the length is 15 μm.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] By adopting the technical solution of the present invention, a layer of Fe and Ti is deposited by electron beam to give the spiral micro-nano robot magnetic properties and biocompatibility, and then a layer of amino groups is modified on the spiral surface by gold-sulfur bond reaction, and hyaluronidase (HAase) is connected to the spiral surface by glutaraldehyde. The HAase on the surface of the spiral micro-nano robot can catalytically decompose HA, and the magnetically driven spiral micro-nano robot can achieve drag-reducing motion in a viscous solution. The technical solution of the present invention provides a reference for the efficient and controllable driving of micro-nano robots in complex biological fluids (such as cerebrospinal fluid, vitreous body, joint fluid, and intestinal mucosa). BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of a method for preparing a helical micro-nano robot modified by a biological enzyme.
[0021] Figure 2 It is a schematic diagram of the drag reduction method of the helical micro-nano robot modified by biological enzymes in a viscous solution in the present invention.
[0022] Figure 3 It is a bar graph showing the variation of the magnetically driven motion speed of the helical micro-nano robot with or without HAase modification in Example 1 of the present invention with the HA concentration under a magnetic field of 8 mT and 1 Hz.
[0023] Figure 4 is the distance that the spiral microrobot in Example 1 of the present invention moves in a 6 mg / mL sodium hyaluronate solution for 10 s, wherein (a) is unmodified hyaluronidase; (b) is modified hyaluronidase.
[0024] Figure 5 It is a bar graph showing the variation of magnetically driven motion speed of the helical micro-nano robot with or without HAase modification in Example 2 of the present invention with HA concentration under a magnetic field of 8mT and 1Hz; wherein, the helical micro-robot with enzyme refers to the helical micro-robot modified with HAase, and the helical micro-robot without enzyme refers to the helical micro-robot not modified with HAase.
[0025] Figure 6It is a bar graph of the movement speed of the helical microrobot with or without HAase modification in Example 3 of the present invention in a 6 mg / mL sodium hyaluronate solution; wherein, the enzyme refers to the helical microrobot modified with HAase, and the enzyme-free refers to the helical microrobot without HAase modification. DETAILED DESCRIPTION
[0026] The preferred embodiments of the present invention are described in further detail below.
[0027] An anti-adhesive helical micro-nano robot based on bioenzyme modification, such as Figure 1 As shown, the preparation method thereof comprises the following steps:
[0028] Step S1, preparation of magnetically controlled helical micro-nano robot: using a two-photon 3D printer on a 22*22mm 2 A spiral array was printed on a glass slide, and then a layer of Fe and Ti was evaporated using a high-vacuum electron beam evaporation coating machine to give the spiral micro-nano robot magnetic and biocompatibility.
[0029] The specific materials and preparation processes are as follows: a PPGT2 two-photon 3D printer produced by Nanoscribe of Germany was selected, and IP-S photoresist was used to prepare a 3D printer with a thickness of 0.16 mm and a size of 22*22 mm. 2 A double helix array with a diameter of 6 μm and a length of 20 μm was printed on a glass slide. The laser power was set to 40 mW and the scanning speed was 100 mm / s. After printing, it was developed and dried with 99.5% isopropanol. Then, a high vacuum electron beam evaporation coating machine was used to evaporate Fe and Ti. First, an 80 nm Fe layer was evaporated to give the spiral micro-nano robot magnetism, and then a 10 nm Ti layer was evaporated to give the micro-nano robot biocompatibility. The vacuum degree was controlled at 10 -4 Below, the sample stage rotation speed is 8 rpm to ensure the uniformity of the coating.
[0030] Step S2, enzyme modification of the surface of the spiral micro-nano robot: a layer of gold film is plated on the glass slide treated by S1, and then the glass slide is immersed in a β-mercaptoethylamine solution to react, a layer of amino groups is modified on the spiral surface through a gold-sulfur bond reaction, and then hyaluronidase (HAase) is connected to the spiral surface with glutaraldehyde.
[0031] The specific experimental preparation process is as follows: a layer of gold film is plated on the spiral surface using a SBC12 small ion sputtering instrument, and the sputtering current is controlled to be 5 mA and the sputtering time is 330 s; then a 10 μM β-mercaptoethylamine solution is prepared, and the gold-plated glass slide is placed in the prepared β-mercaptoethylamine solution for oscillation reaction for 4 hours to modify the spiral surface with amino groups; then the material is rinsed with pure water 3-5 times, and then the glass slide is placed in a PBS solution of glutaraldehyde for 4 hours (V PBS / V戊二醛 =70 / 1); then rinse the material sheet with pure water for 3-5 times, then add PBS solution (2.5mg / mL) of hyaluronidase (HAase) to react overnight, and select the concentrated high-activity (3000U / mg) sample produced by Shanghai Yuanye for HAase to obtain a spiral array modified with hyaluronidase (HAase). Then rinse the spiral surface with pure water for 3-5 times to fully wash off the unconnected hyaluronidase, and then cut the spiral array with a glass knife and put it into a transparent centrifuge tube with a capacity of 1.5mL, add 0.5mL of water, and put the centrifuge tube into an ultrasonic machine for 1min to form a uniform dispersion of the spiral. The control group used the spirals without modified HAase to prepare the same volume of spiral dispersion.
[0032] The anti-adhesive helical micro-nano robot prepared above based on bio-enzyme modification has HAase enzyme on its surface, which can catalyze the decomposition of HA, thereby realizing the drag reduction performance of the magnetically driven helical micro-nano robot in HA solution. Figure 2 The specific research experiment includes the following steps:
[0033] Sodium hyaluronate (HA) solution of appropriate concentration was prepared, HA and spiral solution were added into the groove of 10mm×10mm acrylic plate in sequence, and then the plate was placed under a three-axis Helmholtz coil for magnetic drive experiment. The magnetic field related parameters were adjusted, and the magnetic control motion video was observed and filmed under a 10x eyepiece × 20x objective microscope. The movement speed of the spiral micro-nano robot with and without enzyme modification was observed and compared, and the movement speed was calculated and the data was summarized.
[0034] The specific process flow is as follows: prepare a HA (①H107141 sodium hyaluronate, derived from Streptococcus equi, 95%) solution with a concentration of 6 mg / mL, heat it in a 90°C water bath for 30 minutes and stir to fully dissolve the HA powder. First add 6 mg / mL HA (100 μL) to the 10×10 mm groove, then add the spiral dispersion (40 μL), and finally add 6 mg / mL HA (100 μL), then cover the slide to make the spiral solution completely dispersed in the HA solution; then stick a 30*40 mm polyimide heating film (5V1W) on the bottom of the groove, and connect a DC power supply, set the voltage to 4.5V, the current to 0.2A, and heat for 5 minutes to achieve uniform mixing of the spiral solution and HA, and keep the temperature at 37°C. Then put the groove into the working range of the three-axis Helmholtz coil, apply a rotating magnetic field, and establish the motion speed distribution diagram of the spiral microrobot by adjusting the magnetic field intensity and rotation frequency. Through preliminary exploratory experiments, the magnetic field parameters were locked at 8mT and magnetically driven movement was performed at 1Hz. The experimental group and the control group respectively shot more than 5 videos of spiral movement for 20s, observed and compared the difference in movement speed of the spiral micro-nano robot with and without enzyme modification, calculated the movement speed, and summarized the data to draw a speed curve.
[0035] The following describes the invention in conjunction with specific embodiments.
[0036] Example 1
[0037] The above method was used to prepare a helical micro-nano robot modified by biological enzymes, and its drag reduction performance in viscous HA solution was studied. Specifically, it includes:
[0038] (1) Using a two-photon 3D printer and IP-S photoresist, the thickness of the 3D printer is 0.16 mm and the size is 22*22 mm. 2 A double helix array with a diameter of 6 μm and a length of 20 μm was printed on a glass slide. The laser power was set to 40 mW and the scanning speed was 100 mm / s. After printing, it was developed and dried with 99.5% isopropanol. Then, a high vacuum electron beam evaporation coating machine was used to evaporate Fe and Ti. The 80 nm Fe layer was evaporated to give the spiral micro-nano robot magnetic properties, and then the 10 nm Ti layer was evaporated to give the micro-nano robot biocompatibility. The vacuum degree was controlled at 10 -4 Below, the sample stage rotation speed is 8 rpm to ensure the uniformity of the coating.
[0039] (2) A layer of gold film was plated on the spiral surface using a SBC12 small ion sputtering apparatus, with the sputtering current controlled to 5 mA and the sputtering time to 330 s. A 10 μM β-mercaptoethylamine solution was then prepared, and the gold-plated glass slide was placed in the prepared β-mercaptoethylamine solution for 4 h of oscillation reaction to modify the spiral surface with amino groups. The material was then rinsed with pure water for 3-5 times, and the glass slide was then placed in a PBS solution of glutaraldehyde for 4 h (V PBS / V 戊二醛 =70 / 1); then rinse the material sheet with pure water for 3-5 times, then add PBS solution of hyaluronidase (2.5mg / mL) to react overnight, and select concentrated high-activity (3000U / mg) sample produced by Shanghai Yuanye for hyaluronidase (HAase) to obtain a spiral array modified with hyaluronidase (HAase). Then rinse the spiral surface with pure water for 3-5 times to fully wash off the unconnected hyaluronidase, and then cut the spiral array with a glass knife and put it into a transparent centrifuge tube with a capacity of 1.5mL, add 0.5mL of water, and put the centrifuge tube into an ultrasonic machine for 1min to form a uniform dispersion of the spiral. The control group used the spiral of unmodified HAase to prepare the same volume of spiral dispersion.
[0040] (3) Prepare HA (①H107141 sodium hyaluronate, derived from Streptococcus equi, 95%) solutions with concentrations of 9, 6, and 3 mg / mL, respectively, and heat in a 90°C water bath for 30 min and stir to fully dissolve the HA powder. First add HA (100 μL) to the 10×10 mm groove, then add the spiral dispersion (40 μL), and finally add HA (100 μL), and then cover with a glass slide to allow the spiral solution to be completely dispersed in the HA solution; then stick a 30*40 mm polyimide heating film (5V1W) on the bottom of the groove, and connect a DC power supply, set the voltage to 4.5 V, the current to 0.2 A, and heat for 5 min to achieve uniform mixing of the spiral solution and HA, and keep the temperature at 37°C. Then put the groove into the rotating magnetic field of the three-axis Helmholtz coil, and establish the cluster formation phase diagram by adjusting the magnetic field rotation frequency and magnetic field intensity. Through preliminary exploratory experiments, the magnetic field parameters were locked at 8mT and magnetically driven movement was performed at 1Hz. Three experimental groups (9, 6 and 3mg / mL of HA) and a control group each shot videos of more than 5 spiral movements for 20s. The movement speeds of the spiral micro-nano robots with and without enzyme modification were observed and compared. The movement speed was calculated and the data was summarized to draw a speed curve.
[0041] The movement speed of the helix with and without HAase modification in HA solutions of different concentrations is as follows Figure 3 and Figure 4As shown in the experimental results, the movement speed of the helix modified with hyaluronidase in 3mg / mL and 9mg / mL HA solutions is not much different, and is higher than that of the helix without modified enzyme; Figure 4 The video snapshots of the movement of the helix modified enzyme before and after 6 mg / mL within 10 seconds also show that the movement speed of the helix modified with hyaluronidase is significantly faster than that of the unmodified helix. This indicates that hyaluronidase can play a decomposition role at 37°C, reducing the concentration of surrounding HA, thereby increasing the movement speed of the helix.
[0042] Example 2
[0043] This embodiment includes the following steps:
[0044] (1) Select the PPGT2 two-photon 3D printer and use IP-S photoresist to print a 3D image with a thickness of 0.16 mm and a size of 22*22 mm. 2 A double helix array with a diameter of 4.5 μm and a length of 15 μm was printed on a glass slide. The laser power was set to 40 mW and the scanning speed was 100 mm / s. After printing, it was developed and dried with 99.5% isopropanol. Then, a high vacuum electron beam evaporation coating machine was used to evaporate Fe and Ti. The 80 nm Fe layer was evaporated to give the spiral micro-nano robot magnetic properties, and then the 10 nm Ti layer was evaporated to give the micro-nano robot biocompatibility. The vacuum degree was controlled at 10 -4 Below, the sample stage rotation speed is 8 rpm to ensure the uniformity of the coating.
[0045] (2) A layer of gold film was plated on the spiral surface using a SBC12 small ion sputtering apparatus, with the sputtering current controlled to 5 mA and the sputtering time to 300 s. A 20 μM β-mercaptoethylamine solution was then prepared, and the gold-plated glass slide was placed in the prepared β-mercaptoethylamine solution for 4 h of oscillation reaction to modify the spiral surface with amino groups. The material was then rinsed with pure water for 3-5 times, and the glass slide was then placed in a PBS solution of glutaraldehyde for 4 h (V PBS / V 戊二醛 =70 / 1); then rinse the material sheet with pure water for 3-5 times, then add PBS solution of hyaluronidase (5mg / mL) to react overnight, and select concentrated high-activity (3000U / mg) sample produced by Shanghai Yuanye for hyaluronidase (HAase) to obtain a spiral array modified with hyaluronidase (HAase). Then rinse the spiral surface with pure water for 3-5 times to fully wash off the unconnected hyaluronidase, and then cut the spiral array with a glass knife and put it into a transparent centrifuge tube with a capacity of 1.5mL, add 0.5mL of water, and put the centrifuge tube into an ultrasonic machine for 1min to form a uniform dispersion of the spiral. The control group used the spiral of unmodified HAase to prepare the same volume of spiral dispersion.
[0046] (3) This time, the experiment was refined on the basis of Example 1, specifically including: preparing HA (①H107141 sodium hyaluronate, derived from Streptococcus equi, 95%) solutions with concentrations of 9, 7.5, 6, 4.5 and 3 mg / mL respectively, heating in a 90°C water bath for 30 min and stirring to fully dissolve the HA powder. First add HA (100 μL) to the 10×10 mm groove, then add the spiral dispersion (40 μL), and finally add HA (100 μL), and then cover with a glass slide to make the spiral solution completely dispersed in the HA solution; then stick a 30*40 mm polyimide heating film (5V1W) on the bottom of the groove, and connect a DC power supply, set the voltage to 4.5V, the current to 0.2A, and heat for 5 min to achieve uniform mixing of the spiral solution and HA, and keep the temperature at 37°C. Then put the groove into the rotating magnetic field of the three-axis Helmholtz coil, and establish the cluster formation phase diagram by adjusting the magnetic field rotation frequency and magnetic field intensity. Through preliminary exploratory experiments, the magnetic field parameters were locked at 8mT and magnetically driven movement was performed at 1Hz. Five experimental groups (9, 7.5, 6, 4.5 and 3mg / mL HA) and a control group each shot videos of more than 5 spiral movements for 20s. The movement speeds of the spiral micro-nano robots with and without enzyme modification were observed and compared, and the movement speeds were calculated and the data were summarized to draw a speed curve.
[0047] The experimental results are as follows Figure 5 As shown, it can be observed that the decrease in the size of the helix leads to a decrease in speed. As the HA concentration increases, the speed of the helix gradually decreases. It is particularly noteworthy that in HA solutions with concentrations of 6 and 7.5 mg / mL, the speed of the helix structure modified with hyaluronidase is significantly faster than that of the unmodified helix structure. The movement speed of the helix modified with hyaluronidase in HA solutions with concentrations of 3 mg / mL and 9 mg / mL is not much different, and is higher than that of the helix of the unmodified enzyme, indicating that hyaluronidase can play a decomposing role at 37°C, reducing the concentration of surrounding HA, thereby increasing the movement speed of the helix.
[0048] Example 3
[0049] This embodiment includes the following steps:
[0050] (1) Select a PPGT2 two-photon 3D printer and use IP-S photoresist to print a double helix array with a diameter of 6 μm and a length of 20 μm on a glass sheet with a thickness of 0.16 mm and a size of 22*22 mm2. Set the laser power to 40 mW and the scanning speed to 100 mm / s. After printing, use 99.5% isopropyl alcohol to develop and dry. Then use a high vacuum electron beam evaporation coating machine to evaporate Fe and Ti. Evaporate a 50 nm Fe layer to give the spiral micro-nano robot magnetism, and then evaporate 10 nm Ti to give the micro-nano robot biocompatibility. The vacuum degree during the evaporation process is controlled at 10 -4 Below, the sample stage rotation speed is 8 rpm to ensure the uniformity of the coating.
[0051] (2) In this example, the reaction time of β-mercaptoethylamine and gold film was extended (from 4 h to 24 h) based on Example 1: a layer of gold film was plated on the spiral surface using a SBC12 small ion sputtering apparatus, and the sputtering current was controlled to be 5 mA and the sputtering time was 200 s; then a 20 μM β-mercaptoethylamine solution was prepared, and the gold-plated glass slide was placed in the prepared β-mercaptoethylamine solution for oscillation reaction for 24 h to modify the spiral surface with amino groups; then the material was rinsed with pure water for 3-5 times, and then the glass slide was placed in a PBS solution of glutaraldehyde for reaction for 4 hours (V PBS / V 戊二醛 =70 / 1); then rinse the material sheet with pure water for 3-5 times, then add PBS solution of hyaluronidase (5mg / mL) to react overnight, and select the medicine produced by Aladdin (≥300U / mg) for hyaluronidase (HAase) to obtain a spiral array modified with hyaluronidase (HAase). Then rinse the spiral surface with pure water for 3-5 times to fully wash off the unconnected hyaluronidase, and then cut the spiral array with a glass knife and put it into a transparent centrifuge tube with a capacity of 1.5mL, add 0.5mL of water, and put the centrifuge tube into an ultrasonic machine for 1min to form a uniform dispersion of the spiral. The control group used the spirals without HAase to prepare the same volume of spiral dispersion.
[0052] (3) Prepare a HA (①H107141 sodium hyaluronate, derived from Streptococcus equi, 95%) solution with a concentration of 6 mg / mL, heat in a 90°C water bath for 30 min and stir to fully dissolve the HA powder. First add HA (100 μL) to the 10×10 mm groove, then add the spiral dispersion (40 μL), and finally add HA (100 μL), then cover with a glass slide to allow the spiral solution to be completely dispersed in the HA solution; then stick a 30*40 mm polyimide heating film (5V1W) on the bottom of the groove, and connect a DC power supply, set the voltage to 4.5 V, the current to 0.2 A, heat for 5 min to achieve uniform mixing of the spiral solution and HA, and keep the temperature at 37°C. Then place the groove under a rotating magnetic field of a three-axis Helmholtz coil, and establish a cluster formation phase diagram by adjusting the magnetic field rotation frequency and magnetic field intensity. Through preliminary exploratory experiments, the magnetic field parameters were locked at 8mT and magnetically driven movement was performed at 1Hz. The experimental group and the control group respectively shot more than 5 videos of spiral movement for 20s, observed and compared the difference in movement speed of the spiral micro-nano robot with and without enzyme modification, calculated the movement speed, and summarized the data to draw a speed curve.
[0053] The experimental results are as follows Figure 6 As shown, it can be observed that the drag reduction effect of the spiral micro-nano robot in HA can still be achieved by changing the type of hyaluronidase, but the enzyme activity is reduced and the drag reduction effect is also reduced. In a HA solution with a concentration of 6 mg / mL, the speed of the helical structure modified with hyaluronidase is about twice that of the unmodified helical structure, indicating that the anti-adhesive helical micro-nano robot based on biological enzyme modification in this embodiment still has a drag reduction effect.
[0054] From the above experimental operation process and experimental results, it is not difficult to see that the helical micro-nano robot modified with hyaluronidase (HAase) exhibits significant drag reduction performance in 37°C sodium hyaluronate solution.
[0055] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for preparing an anti-adhesive helical micro-nano robot based on biological enzyme modification, characterized in that: The steps include: Step S1, preparing a spiral micro-nano robot, and sequentially evaporating a layer of Fe and a layer of Ti on the surface of the spiral micro-nano robot to obtain a magnetically controlled spiral micro-nano robot; Step S2, coating a layer of gold film on the surface of the magnetically controlled spiral micro-nano robot, then immersing it in a β-mercaptoethylamine solution for reaction, modifying a layer of amino groups on the spiral surface through a gold-sulfur bond reaction, and then connecting hyaluronidase to the spiral surface of the spiral micro-nano robot with glutaraldehyde to obtain an anti-adhesive spiral micro-nano robot based on biological enzyme modification.
2. The method for preparing the anti-adhesive helical micro-nano robot based on bioenzyme modification according to claim 1, characterized in that: In step S1, a spiral micro-nano robot is printed on a glass sheet using a 3D printer, and then a layer of Fe and Ti is sequentially evaporated on the glass sheet using a high vacuum electron beam evaporation coating machine.
3. The method for preparing the anti-adhesive helical micro-nano robot based on bioenzyme modification according to claim 2, characterized in that: The step S1 comprises: using IP-S photoresist to print a double spiral array on a glass sheet, setting the laser power to 40 mW and the scanning speed to 100 mm / s, and developing and drying with isopropyl alcohol after printing.
4. The method for preparing the anti-adhesive helical micro-nano robot based on bioenzyme modification according to claim 3, characterized in that: The step S1 includes: using a high vacuum electron beam evaporation coating machine to evaporate an 80nm Fe layer, and then evaporate a 10nm Ti layer; during the evaporation process, the vacuum degree is controlled at 10 -4 Hereinafter, the sample stage rotation speed is 6-10 rpm.
5. The method for preparing the anti-adhesive helical micro-nano robot based on bioenzyme modification according to claim 2, characterized in that: In step S2, a layer of gold film is plated on the glass slide treated in step S1, and then the glass slide is immersed in a 5-15 μM β-mercaptoethylamine solution for reaction for more than 3 hours to modify the amino group on the spiral surface to obtain an amino-modified glass slide; then the amino-modified glass slide is placed in a glutaraldehyde PBS solution for reaction for more than 3 hours, and after rinsing, a hyaluronidase PBS solution is added to react overnight.
6. The method for preparing the anti-adhesive helical micro-nano robot based on bioenzyme modification according to claim 5, characterized in that: The PBS solution of glutaraldehyde is prepared by mixing glutaraldehyde and PBS solution in a volume ratio of 1:60-80, and the concentration of the PBS solution is 2-3 mg / mL.
7. The method for preparing the anti-adhesive helical micro-nano robot based on bioenzyme modification according to claim 6, characterized in that: Step S2 also includes: cutting the processed spiral micro-nano robot with a glass cutter and placing it in a container, adding water, and ultrasonically dispersing it to obtain a spiral dispersion.
8. An anti-adhesive helical micro-nano robot based on bio-enzyme modification, characterized by: The anti-adhesive helical micro-nano robot is prepared by the preparation method of the bio-enzyme-modified anti-adhesive helical micro-nano robot as described in any one of claims 1 to 7.
9. Application of the anti-adhesive helical micro-nano robot based on bio-enzyme modification as claimed in claim 8: controllably moving in viscous biological fluids containing HA for targeted drug delivery.
Citation Information
Patent Citations
Magnetic control micro-nano robot and manufacturing method and application thereof
CN115196585A
Magnetic control miniature spiral robot
CN212631236U
Biomimetic bioengine yeast micro / nanorobot and preparation method therefor
WO2023104125A1
